Photosensitizing role of R-phycoerythrin red protein and β-carboline alkaloids in Dye sensitized solar cell: Electrochemical and spectroscopic characterization - Juan G. Ya\~nuk; Franco M. Cabrerizo; Fernando G. Dellatorre; María F. Cerdá (Energy Reports, 2020)
Dye-sensitized solar cell (DSSC) technology represents a valuable source for renewable energy production. Although with a rather low conversion efficiency, the continuous improvement of the price/performance ratio is making this technology more competitive than other sources of electrical power generation. To date, one of the major challenges is the search of novel and low-cost photosensitizers, a key player in the overall photo-conversion process. Natural dyes have shown to be an excellent alternative that still needs to be further explored. In this work, the spectroscopic and electrochemical properties of two different families of naturally occurring pigments (i.e, -carboline alkaloids (Cs) and the red protein R-phycoerythrin (R-PE)) as well as their role in DSSCs are addressed. DSSC assemblies show that R-PE represents a highly suitable photosensitizer showing quite a high stability with a relative high solar energy to electricity conversion efficiency (n=0.11%) when comparing with other recombinant proteins ( n=0.30%). Algae extracts used without further purification showed herein the highest efficiencies. The latter fact has a concomitant positive effect on the overall production cost of these photovoltaic cells. Surprisingly, and despite their positive effect on the coating of the semiconductor surface, the use of Cs as additive decreases the overall conversion efficiency of the R-PE based DSSCs evaluated. Data support the hypothesis these alkaloids would be blocking the incident UVB/UVA radiation.
Keywords: 330